MAGMATIC FLUID INCLUSIONS FROM THE ZALDíVAR DEPOSIT NORTHERN CHILE: THE ROLE OF EARLY METAL-BEARING FLUIDS IN A PORPHYRY COPPER SYSTEM - Campos E.A.; Touret J.L.R.; Nikogosian I. (My University, 2006)
The occurrence of a distinct type of multi-solid, highly-saline fluid inclusions, hosted in igneous quartz phenocrysts from the Llamo porphyry, in the Zaldívar porphyry copper deposit of northern Chile is documented. Total homogenization of the multi-solid type inclusions occurs at magmatic temperatures (over 750°C), well above the typical temperatures of hydrothermal fluids (less than 600°C) usually recorded in porphyry copper systems. The analysis of this type of fluid inclusions, using a combination of non-destructive microthermometry, Raman and PIXE techniques and the identification of daughter minerals by SEM method, indicates that the trapped fluid was a dense, complex chloride brine in which Cl, Na, K, Fe, Cu, and Mn are dominant. The high chlorine and metal contents indicate that the metals were separated from the crystallizing magma as homogeneous aqueous chloride-rich solutions that represent the primary magmatic fluids exsolved at high temperatures and depth during the crystallization of the parental intrusive. The multi-solid type inclusion illustrates the mechanism by which ore components are sequestered from the crystallizing parental magma and concentrated in the exsolved magmatic aqueous fluids. These fluids are significant with respect to the origin of porphyry copper deposits, as they are responsible for the first enrichment of metals and represent the precursors of metal-bearing hydrothermal fluids in a porphyry copper system.
Keywords: FLUID INCLUSIONS; MAGMATIC HYPERSALINE FLUIDS; METAL-BEARING FLUIDS; PORPHYRY COPPER DEPOSITS; ZALDÍVAR PORPHYRY DEPOSIT